International new venture legitimation: An exploratory study - Romeo V. Turcan (Administrative Sciences, 2013)
There is limited theoretical understanding and empirical evidence for how international new ventures legitimate. Drawing from legitimation theory, this study fills in this gap by exploring how international new ventures legitimate and strive for survival in the face of critical events during the process of their emergence. It is a longitudinal, multiple-case study research that employs critical incident technique for data collection, analysis, and interpretation. Following theory driven sampling, five international new ventures were selected that were operating in the software sector in the UK, and had internationalized and struggled for survival during the dotcom era. Grounded in data, this study corroborates a number of legitimation strategies yielded by prior research and refutes others. It further contributes to our understanding of international new venture legitimation by suggesting new types of legitimation strategies: technology, operating, and anchoring. Studying international new ventures through theoretical lenses of legitimation is a promising area of research that would contribute to the advancement of international entrepreneurship theory.
Keywords: 350; international new venture; legitimation; dotcom; case study; theory building; international entrepreneurship